2020
DOI: 10.3390/pathogens9030186
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Recent 2019 Novel Coronavirus (SARS-CoV-2) in Light of Past Human Coronavirus Outbreaks

Abstract: Coronaviruses (CoVs) are RNA viruses that have become a major public health concern since the Severe Acute Respiratory Syndrome-CoV (SARS-CoV) outbreak in 2002. The continuous evolution of coronaviruses was further highlighted with the emergence of the Middle East Respiratory Syndrome-CoV (MERS-CoV) outbreak in 2012. Currently, the world is concerned about the 2019 novel CoV (SARS-CoV-2) that was initially identified in the city of Wuhan, China in December 2019. Patients presented with severe viral pneumonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
536
0
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(572 citation statements)
references
References 112 publications
(162 reference statements)
1
536
0
35
Order By: Relevance
“…El uso de mascarillas quirúrgicas no protege totalmente y se recomienda no tocar la cara y especialmente los ojos y mucosas con las manos. El lavado de manos durante 30 segundos con agua y jabón así como la desinfección de superficies es efectiva frente a la transmisión 1,2,5 .…”
Section: El Covid-19unclassified
“…El uso de mascarillas quirúrgicas no protege totalmente y se recomienda no tocar la cara y especialmente los ojos y mucosas con las manos. El lavado de manos durante 30 segundos con agua y jabón así como la desinfección de superficies es efectiva frente a la transmisión 1,2,5 .…”
Section: El Covid-19unclassified
“…Hydrophobic region oligomerise and form an ion-conductive pore in membranes. This protein play key role in various phases of the virus' life cycle, such as envelope formation, pathogenesis, budding and assembly (Ashour et al, 2020;Schoeman & Fielding, 2019). Few studies have also suggested that the 'SARS-CoV E' proteins' ion channel activity is modulated via pentameric ion channel (Pervushin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At first, many individuals and nations assumed that it would be contained within China due to rapid implementation of quarantine for the city of Wuhan and the remarkable construction of two hospitals in only 12 days. The zoonotic transmission of COVID-19 from wildlife to humans led to a Chinese ban on wildlife trade; however, the rapid spread of COVID-19 shows a systematic and expeditious transmission between humans [2].…”
Section: Editorialmentioning
confidence: 99%